Efek Imunomodulator Ekstrak Etanol Herba Krokot (Portulaca oleracea L.) terhadap Tikus Putih (Rattus norvegicus) Jantan dengan Parameter Delayed Type Hypersensitivity (DTH): Effect of Immunomodulator of Purslane Herb Ethanol (Portulaca oleracea L.) on Rat (Rattus norvegicus) with Delayed Type Hypersensitivity (DTH) Parameter - Putra, Bayu; Azizah, Rizqi Nur; Nopriyanti, Eka Maryam (Universitas Tadulako, 2020)
Portulaca oleracea L. is one of the plants empirically used as medicine and contains flavonoid compounds assumed to have an immunomodulatory effect. The research aimed to determine the immunomodulatory effect of ethanol extract of Portulaca oleracea L by Delayed Type Hypersensitivity parameter. The research used 20 male rats (Rattus norvegicus) divided into 5 groups where each group consisted of 4. Group I as a normal group (without treatment), group II (NaCMC control), group III, IV and V (treatment groups) were given EEHK with doses of 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW doses. The dosage form was orally given for 7 days. On day 3, the rats were induced with SDMD antigen 10% v/v by intraperitonial and intraplantar on day 7. The observations were conducted by measuring the volume change of the rat's feet at the 4th, 24th, and 48th hours using a pletismometer. The research data obtained were statistically processed using Paired Samples T Test, One-Way Anova and Post Hoc LSD tests. The results of the research showed that the ethanol extract of common purslane was effective as an immunomodulator.